Lagrange multiplier rules for weak approximate Pareto solutions to constrained vector optimization problems with variable ordering structures - Hu, Chunhai; Zhu, Jiangxing (Optimization, 2022)
In this paper, we consider the weak approximate solutions to constrained vector optimization problems with variable ordering structures. In terms of abstract subdifferentials, normal cones and coderivatives, we establish Lagrange rules for this kind of solutions.